Ruled surfaces in En - Goncharova, O. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
Some local and global properties of ruled surfaces in $E^n$ is devoted to a study. In particular, the total Gauss curvature of the complete regular orientable ruled surface was calculated. Also, Gaussian torsion was investigated, and ruled surfaces in $E^4$ with zero Gaussian torsion were studied in detail. Mathematics Subject Classification: 53A07.